Celecoxib and Etoricoxib may reduce risk of ischemic stroke in patients with rheumatoid arthritis: A nationwide retrospective cohort study - Chen, Acer I-Hung; Lee, Yung-Heng; Perng, Wuu-Tsun; Chiou, Jeng-Yuan; Wang, Yu-Hsun; Lin, Lichi; Wei, James Cheng-Chung; Tsou, Hsi-Kai (Frontiers in Neurology, 2022)
Background and Purpose Previous studies reported conflicting results about the risk of ischemic stroke associated with the use of nonsteroidal anti-inflammatory drugs (NSAIDs) in patients with rheumatoid arthritis (RA). We aimed to investigate two specific COX-2 inhibitors, Celecoxib and Etoricoxib, and their corresponding effects on the risk of ischemic stroke in patients with RA. Patients and Methods 10,857 newly diagnosed patients with RA were identified and sampled from the Taiwanese National Health Insurance Research Database during the period from 2001 to 2009. The identification of RA was based on the criteria of ICD-9-CM diagnosis code 714.0. Patients diagnosed with cerebrovascular disease and those receiving RA treatment prior to the first diagnosis of RA were excluded. Study endpoint was ischemic stroke, defined by ICD-9-CM code. Cox proportional hazard models and Kaplan Meier curves were used to reveal covariates and differences by drugs in the risk of ischemic stroke. Dosages for Celecoxib were defined as ≤200 and >200 mg/day; those for Etoricoxib were 0 and >0 mg/day. Results Among 7,904 RA patients, 6,669 did not take Celecoxib and 564 (8.46%) of them experienced an ischemic stroke event. Of the 597 individuals who took ≤200 mg/day of Celecoxib, 58 (9.72%) had strokes. Of the 638 patients who took >200 mg/day of Celecoxib, 38 (5.96%) eventually experienced a stroke. Among the 7,681 patients who did not take Etoricoxib, 654 (8.51%) experienced an ischemic stroke, while 6 (2.69%) in 223 patients who consumed Etoricoxib had a stroke event. Consuming more than 200 mg of Celecoxib per day for <3.5 years lowered the incidence rate for strokes (hazard ratio [HR] 0.67, 95% Confidence Interval [CI] 0.48-0.93 for dosage and HR 0.22, 95% CI 0.10-0.46 for duration, both p<0.001), while consuming any dosage of Etoricoxib significantly decreases the possibility (HR 0.35, 95% CI 0.16-0.80, p<0.001). On the other hand, consuming Etoricoxib for 8 years might have a neutral or even a potentially protective effect compared to at 3.8 years. Conclusion This population-based retrospective cohort study has shown that Celecoxib and Etoricoxib reduce the risk of ischemic stroke in patients with RA in a dose- and time-dependent manner.